2016
DOI: 10.1111/acem.12862
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the National Hospital Ambulatory Medical Care Survey: United States Emergency Department Opioid Prescribing, 2006–2010

Abstract: Objective Prescription opioid overdoses are a leading cause of death in the United States. Emergency departments (EDs) are potentially high risk environments for doctor shopping and diversion. We hypothesized that opioid prescribing rates from the ED have increased over time. Methods We analyzed data on ED discharges from the 2006–2010 NHAMCS, a probability sample of all United States EDs. The outcome was documentation of an opioid prescription on discharge. The primary independent predictor was time. Covari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 21 publications
(23 reference statements)
4
49
0
Order By: Relevance
“…3 Some policymakers and members of the public perceive EDs to be a significant source of overprescription of opioids. 4–6 This perception may stem from the fact that many ED visits involve chronic or acute pain; adult patients reported pain as the primary symptom in 45% of ED visits. 7 With so many patients in pain, it isn’t surprising that recent studies have found that 17-21% of all ED discharges included a prescription for opioids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Some policymakers and members of the public perceive EDs to be a significant source of overprescription of opioids. 4–6 This perception may stem from the fact that many ED visits involve chronic or acute pain; adult patients reported pain as the primary symptom in 45% of ED visits. 7 With so many patients in pain, it isn’t surprising that recent studies have found that 17-21% of all ED discharges included a prescription for opioids.…”
Section: Introductionmentioning
confidence: 99%
“…7 With so many patients in pain, it isn’t surprising that recent studies have found that 17-21% of all ED discharges included a prescription for opioids. 4,8 …”
Section: Introductionmentioning
confidence: 99%
“…Emergency department data from the United States indicate that opioid use increased 90% between 2001 and 2010, and that opioids were prescribed at discharge to almost 20% of patients. [10][11][12] Although most emergency physicians likely consider opioid medications safe for the relief of acute pain and may therefore regard their role in the current opioid crisis to be limited to preventing diversion, recent reports suggest that opioids prescribed in the emergency department, especially to opioidnaive patients, are associated with substantial morbidity. [13][14][15] In 2014-2015, there were 4779 hospital admissions due to opioid toxicity in Canada, representing a total of 38 405 days of care provided in Canadian hospitals to patients admitted with a diagnosis of opioid toxicity.…”
mentioning
confidence: 99%
“…From a community standpoint, prior studies have highlighted the importance of community-based approaches to prevent opioid-related deaths [83], yet none have been explored in the context of GI care. Kea et al have suggested that problems with inappropriate opioid use are multifactorial in nature and not linked with a specific care setting, patient characteristic or provider type [84]. This suggests that interventions grounded in the CCM that actively engage patients, providers, health systems and communities may be especially beneficial.…”
Section: Discussionmentioning
confidence: 99%